2017
DOI: 10.1371/journal.pone.0184295
|View full text |Cite
|
Sign up to set email alerts
|

ABO blood type and the risk of cancer – Findings from the Shanghai Cohort Study

Abstract: ABO blood type is an inherited characteristic. The associations between ABO blood type and risk of all cancer and specific cancers were examined in a prospective cohort study of 18,244 Chinese men enrolled in 1986. During the 25 years of follow-up, 3,973 men developed cancer including 964 lung cancers, 624 colorectal cancers, 560 gastric cancers, 353 liver cancers, and 172 urinary bladder cancers. Hazard ratios (HR) for all cancer and specific cancers by ABO blood type were calculated using Cox proportional ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

3
51
1
1

Year Published

2019
2019
2023
2023

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 52 publications
(56 citation statements)
references
References 34 publications
3
51
1
1
Order By: Relevance
“…but not related to the risk of sarcoma, lymphoma, leukemia or other cell types of cancer. [8] A retrospective study by Li et al showed that there is an association between the ABO blood types and the survival of Chinese patients with resected NSCLC. And the overall survival, patients-free survival and locoregional relapse-free survival were signi cantly prolonged in patients with a blood group of O or B compared with patients with blood group A or AB.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…but not related to the risk of sarcoma, lymphoma, leukemia or other cell types of cancer. [8] A retrospective study by Li et al showed that there is an association between the ABO blood types and the survival of Chinese patients with resected NSCLC. And the overall survival, patients-free survival and locoregional relapse-free survival were signi cantly prolonged in patients with a blood group of O or B compared with patients with blood group A or AB.…”
Section: Discussionmentioning
confidence: 99%
“…[6] Chang et al showed that type A blood is associated with a higher incidence and metastatic rate of malignant melanoma of the skin, [7] blood type B It also signi cantly reduced the risk of stomach cancer and bladder cancer, while blood type AB signi cantly increased the risk of liver cancer. [8] Moreover, studies have shown that ABO blood type has no effect on the survival of patients with epithelial ovarian cancer. [9] Previous studies have shown that regardless of menopausal status, body mass index, oral contraceptive use or family cancer history, blood group A is positively associated with EC risk in Chinese women [10] .…”
Section: Introductionmentioning
confidence: 99%
“…In a cohort study of 18,244 Chinese blood donors in 1986 who were followed up for 26 years, 560 of them developed gastric cancer. The result showed that group A was associated with higher incidences of gastric cancer, while group A, AB and O were associated with reduced incidences of all cancers [29].…”
Section: Abo Blood Group and Gastric Cancermentioning
confidence: 95%
“…After the discovery of a relationship between gastric cancer and blood group-A in 1953, studies were conducted on the possible relationship between blood groups and certain diseases (7). In a prospective study of a cohort of middle-aged and elderly Chinese males by Huang et al (8) the overall risk of cancer was lower for the blood group B and lower in the B and AB blood groups compared to the blood group A in gastrointestinal cancers, including gastric and colorectal cancer.In contrast, this study showed a higher risk of liver cancer for the blood group AB and a lower risk of bladder cancer for the blood group B. These findings suggest that in addition to red blood cells, ABO blood group antigens are also expressed in epithelial cells of the gastrointestinal and urinary tract and the role of ABO blood groups in the development of epithelial cancers in the gastrointestinal and urinary tract.…”
Section: Introductionmentioning
confidence: 99%
“…Since Aird et al (7) first reported the relationship between peptic ulcer and gastric carcinoma and ABO blood groups, several studies have been conducted on this issue. Previous studies, mostly in Western populations, have found an increased risk of gastric cancer in individuals with blood group A of about 20% (8). All of these studies have demonstrated that the relationship between solid tumors and ABO blood group has been suspected to be the same in hematologic cancers, but there are fewer studies investigating the relationship between hematologic cancers and ABO blood groups.…”
Section: Introductionmentioning
confidence: 99%